Security- as- a- service: enhancing cloud security through managed security solutions - Attarbashi, Zainab; Mohd Aman, Azana Hafizah; Sati, Salem; Maspo, Nur-Adib; Hassan Abdalla Hashim, Aisha (IGI Global Scientific Publishing, 2026)
Cloud computing plays an important role in modern businesses by enabling flexible, efficient storage, analysis, and access to data and applications. However, this reliance also introduces new security challenges. Ensuring cloud security and resilience is now critical to prevent unauthorized access, data breaches, and service disruptions. This chapter examines the key principles, technologies, and policies that uphold the confidentiality, integrity, and availability of cloud systems. It also highlights Security- as- a- Service (SECaaS) as a necessary part of the cloud ecosystem, offering specialized, scalable solutions to improve overall security. By delivering managed security services via the cloud, SECaaS allows organizations to outsource key functions such as threat intelligence, endpoint protection, access control, and compliance monitoring. It can enhance protection without heavy in- house investment